Strontium-doped apatitic bone cements with tunable antibacterial and antibiofilm ability - Dapporto, Massimiliano; Tavoni, Marta; Restivo, Elisa; Carella, Francesca; Bruni, Giovanna; Mercatali, Laura; Visai, Livia; Tampieri, Anna; Iafisco, Michele; Sprio, Simone (Frontiers in Bioengineering and Biotechnology, 2022)
Injectable calcium phosphate cements (CPCs) represent promising candidates for the regeneration of complex-shape bone defects, thanks to self-hardening ability, bioactive composition and nanostructure offering high specific surface area for cell attachment and conduction. Such features make CPCs also interesting for functionalization with various biomolecules, towards the generation of multifunctional devices with enhanced therapeutic ability. In particular, strontium-doped CPCs have been studied in the last years due to the intrinsic antiosteoporotic character of strontium. In this work, a SrCPC previously reported as osteointegrative and capable to modulate the fate of bone cells was enriched with hydroxyapatite nanoparticles (HA-NPs) functionalized with tetracycline (TC) to provide antibacterial activity. We found that HA-NPs functionalized with TC (NP-TC) can act as modulator of the drug release profile when embedded in SrCPCs, thus providing a sustained and tunable TC release. In vitro microbiological tests on Escherichia coli and Staphylococcus aureus strains proved effective bacteriostatic and bactericidal properties, especially for the NP-TC loaded SrCPC formulations. Overall, our results indicate that the addition of NP-TC on CPC acted as effective modulator towards a tunable drug release control in the treatment of bone infections or cancers.